TO THE DIGITALIZATION OF BUSINESS PROCESSES ITSELF SCIENTIFIC APPROACHES TO THE CHARACTERISTICS (American Journal of Research in Humanities and Social Sciences, 2023)
This article is devoted to the study of the specific features of digitization of business processes, classification of business processes from the point of view of digitization, disclosure of advantages and disadvantages of digitization of business processes, systematization of the main tasks of digitization and the results expected from them, and necessary conditions for digitization of business processes are discussed.